Vibration Ball Milling for the Synthesis of 5′‐Thioadenosine 5′‐Pyrophosphate (P′→5′) Adenosine (dASppA). Issue 1 (13th February 2018) - Eguaogie, Olga; Vyle, Joseph S.
Abstract: Using vibration ball milling, 5′‐chloro‐5′‐deoxyadenosine (CldA) reacts cleanly with 4‐methoxybenzyl mercaptan (MobSH), under basic conditions, to the corresponding thioether (MobSdA), which is isolated following precipitation and trituration. Under acidic conditions, in a one‐pot, two‐step process, MobSdA is transformed into 5′‐deoxy‐5′‐(5‐nitropyridyl‐2‐disulfanyl)‐adenosine (NPySSdA). Michaelis‐Arbuzov (M‐A) reaction of NPySSdA with tris(trimethylsilyl) phosphite proceeds to completion within 30 min as determined by 31 P NMR, and the persilylated M‐A product thus formed can be stored in solution under anhydrous conditions at room temperature for several days (in contrast, the anionic phosphorothiolate monoester is labile to hydrolysis). Following evaporation, mechanochemical mixing of the crude M‐A product with the nucleotide donor adenosine 5′‐monophosphomorpholidate under acidic activation in the presence of additional water gives rapid hydrolytic desilylation and phosphate coupling, so that essentially complete reaction is observed after 90 min and dASppA isolated following C‐18 reversed phase HPLC and desalting (>99% pure as determined by monitoring at 260 nm). © 2017 by John Wiley & Sons, Inc.